Responses to growth hormone (GH) therapy in short children with normal GH secretion and no bone age delay: an analysis of potential factors affecting their response to rhGH therapy. A controlled study - Soliman, Ashraf T; Elawwa, Ahmed; Itani, Maya; Jour, Celine; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Variability still exist about the growth response to growth hormone (GH) therapy in children with idiopathic short stature (ISS). We describe the growth response to rhGH therapy for >2 years in 20 prepubertal children with idiopathic short stature (ISS) and 18 children with GH deficiency (GHD) and compared them with 15 children with ISS who did not receive rhGH therapy. Patients and methods: Our study included 35 prepubertal and peripubertal (Tanner 1 and 2) children with short stature (Ht-SDS 1SD below their mid parental height SD (MP-Ht-SDS) with slow growth velocity ( 1 SD below their MP-Ht-SDS.